Mechanisms of Microbial disease (Williams & Wilkins, 1998)
Tufts Univ., Boston, MA. Text of medical microbiology and infectious disease for medical students. Includes case studies, key concepts, review questions with answers, review charts of infectious agents, and halftone and two-tone illustrations. Previous edition: c1993. Softcover. DNLM: Communicable Diseases--microbiologybiology